Structural Analysis of Rotating Baffles in a CO2 Separator - Abdul Rahim, Mohamad Syazwan (IRC, 2016)
Optimization of gas separation technologies is being developed by the researchers in order to find the better solution for improvising current technologies in the market. Precisely, in oil and gas industry, common gases exist are natural gas which comprises of major carbon dioxide and methane. Separation usually achieves based on the percent of purity. Pure carbon dioxide production from methane mixture can be obtained by using several common and novel method. In this study, the effects of having baffles that is located inside the CO2 separator were studied. The movement of mixed gases into the rotating baffle and out of the stationary baffle creates a pressure build up around it resulting in the deflection of the stationary baffle. The effects include the material external structure behavior under the low temperature of the baffles.